Sobre a possibilidade de constituição de uma pedagogia do problema - Luza, Robledo dos Santos (My University, 2014)
The purpose of this investigation is to determine the possibility of constituting a theoretical discourse in order to epistemologically found an educational practice based on problematizing activity as an answer to the following research problem: is it possible to constitute a pedagogy based on problem, considering the epistemological implications of such proposal? It is embedded in the line of research for Philosophy of Education, in the Graduate Program in Education at the University of Caxias do Sul. Through the analysis of the utterances and interpretative analysis of theoretical references, a critical analysis was carried out on the concepts of pedagogy, education and problem, in order to produce wide understanding of these concepts, considering social and cultural aspects related to education and pedagogy, and the epistemological and existential aspects related to the problem. This analysis made it possible to elaborate a concept for pedagogy of problem as the theoretical principle of an educative practice in which the relationship with knowledge will take place by problematizing, which is expressed in a set of presumptions and general characteristics. Among others, theoretical support used was concerning the analysis of meaning for the terms pedagogy and education, works written by Fullat, Cambi, Aranha, Saussure, Barthes, Trabant, and Lyons. As for the relationship between education and the phenomenon of social and cultural reproduction, theoretical support used was mainly works by Durkheim, Herskovits, Althusser, and Bourdieu. Regarding the relationship between pedagogical thinking and the phenomenon of cultural changes, theoretical support came from texts written by Plato, Rousseau, Coménio, and Kant. For problem, as a philosophical and pedagogical issue, theory supporting the analysis was Plato´s dialogue Menon; Aristotle´s conceptions for dialectical problem and questions present in his Organon; the idea for asking, presented by Gadamer in Truth and Method; the implications of the theses proposed by Wittgenstein, concerning traditional philosophic problems and the classification as pseudo problems, as presented in Tractatus and his influence on Schlick and Carnap; the conception for problem presented by Popper in Conjectures and Refutations and The Logic of the Social Science; the conception of problem presented by Dewey in Logic: the theory of inquiry; and Bergson´s work. As a result, the intimate relationship between education, culture and science becomes evident, especially for the reproductive role that the first has in relation to the others. The fact that education catalyses the longings for social and cultural transformation, frequently expressed in pedagogical thinking. The methodological, gnoseological, and existential dimension of human´s predisposition towards asking, questioning, and problematizing. The intrinsic relation existing between problems and knowledge. The possibility of constituting a problematizing pedagogy that is epistemologically coherent. As a relevance, the pedagogical possibility of a problematizing educational practice allow the development of an investigative culture, that may be translated in greater material development (technological conquers) and immaterial development (conceptions, customs and values) for the society is presented.
O objetivo desta investigação é determinar a possibilidade de constituição de um discurso teórico que fundamente epistemologicamente a prática educativa baseada na atividade problematizante, respondendo ao seguinte problema de pesquisa: é possível constituir uma pedagogia do problema, considerando as implicações epistemológicas desta proposta? Ela está inserida na linha de pesquisa de Filosofia da Educação, do Programa de Pós-Graduação em Educação da Universidade de Caxias do Sul. Através da análise de enunciados e da análise interpretativa dos referenciais teóricos, efetuou-se uma análise crítica dos conceitos de pedagogia, de educação e de problema, de modo a produzir uma compreensão ampla destes conceitos, considerando os aspectos sociais e culturais relacionados à educação e à pedagogia, e os aspectos epistemológicos e existenciais relacionados ao conceito de problema. Esta análise permitiu a elaboração de um conceito de pedagogia do problema como o fundamento teórico de uma prática educativa na qual a relação com o conhecimento aconteça pela via da problematização, expresso em um conjunto de pressupostos e características gerais. Entre outros, o suporte teórico utilizado foi, em relação à análise dos significados dos termos pedagogia e educação, os escritos de Fullat, Cambi, Aranha, Saussure, Barthes, Trabant e Lyons. Sobre a relação entre a educação e o fenômeno da reprodução social e cultural, o suporte teórico utilizado foi, principalmente, os escritos de Durkheim, Herskovits, Althusser e Bourdieu. Sobre a relação entre o pensamento pedagógico e o fenômeno da mudança cultural, o suporte teórico foram os textos de Platão, Rousseau, Coménio e Kant. Sobre o problema, enquanto questão filosófica e pedagógica, o suporte teórico foi o diálogo Ménon, de Platão; as concepções de problema dialético e questão em Aristóteles presentes no Órganon; a noção do perguntar, apresentadas por Gadamer em Verdade e Método; as implicações das teses de Wittgenstein, em relação aos problemas filosóficos tradicionais e a sua qualificação como pseudoproblemas, conforme apresentadas no Tractatus e a sua influência em Schlick e Carnap; a concepção de problema apresentada por Popper em Conjecturas e Refutações e A Lógica das Ciências Sociais; a concepção de problema apresentada por Dewey em Lógica: a teoria da investigação; e a obra de Bergson. Como resultado, evidencia-se a íntima relação existente entre a educação, a cultura e a sociedade, principalmente pelo papel reprodutor que a primeira possui em relação às outras. O fato de que a educação catalisa os anseios de transformação social e cultural, expressos, freqüentemente, no pensamento pedagógico. A dimensão metodológica, gnoseológica e existencial da predisposição do ser humano para o perguntar, o questionar e o problematizar. A intrínseca relação existente entre os problemas e o conhecimento. A possibilidade de constituição de uma pedagogia problematizante coerente epistemologicamente. Como relevância, apresenta-se a possibilidade pedagógica de que uma prática educacional problematizante permita o desenvolvimento de uma cultura investigativa, que poderá se traduzir em maior desenvolvimento material (conquistas tecnológicas) e imaterial (concepções, costumes e valores) para a sociedade.
Keywords: Educação; Filosofia da educação; Fundamentos do pensamento pedagógico; Epistemologia da educação; Pedagogia problematizante; Philosophy of education; Principles of pedagogical thinking; Epistemology of education; Problematizing pedagogy